Open data ecosystems: an international comparison. Issue 1 (20th March 2017) - Styrin, Evgeny; Luna-Reyes, Luis Felipe; Harrison, Teresa M.
Abstract : Purpose: In this paper, the authors compare the open government data (OGD) ecosystems of Mexico, Russia and the USA in an effort to extract some of the major points of similarity and differentiation between these countries and to trace how variations in these ecosystems may be related to context-specific historical problems and politics, particularly with regard to the possibility of sustained and institutionalized practice. Design/methodology/approach: The authors take a comparative approach, using a set of concepts commonly applied to the three countries to analyze similarities and differences within this group. The authors gathered textual data and information, the searches for relevant documents guided by a set of concepts or criteria that are frequently used in studies of government's open data readiness assessment. Findings: The authors conclude by focusing on the very different national exigencies that have given rise to open data ecosystems in the three countries, the variations in policy vehicles and implementation schemes that have instantiated open data practices within the three ecosystems and the common challenges that each country faces in institutionalizing OGD programs beyond the tenures of their current executives. Originality/value: OGD is an information policy with near global relevance and increasing application. Practitioners and scholars alike have used the concept of an "ecosystem" to guide their approach to implementing this policy and to theorizing its scope and benefits. The international comparison is original and adds to the current understanding of an ecosystem approach to OGD.